Technological Improvements in Three‐Piece Inflatable Penile Prosthesis Design over the Past 40 Years. (November 2015) - Pastuszak, Alexander W.; Lentz, Aaron C.; Farooq, Ahmer; Jones, Leroy; Bella, Anthony J.
Abstract: Introduction: The advent of the penile prosthesis revolutionized the treatment of erectile dysfunction (ED), resulting in near‐complete treatment efficacy and high patient satisfaction rates. While several types of penile prosthesis are available, the inflatable penile prosthesis (IPP) is the most commonly used device in the United States. Aims: To describe the key modifications to IPPs from the two major manufacturers—American Medical Systems (AMS) and Coloplast—since the invention of the IPP, and to relate these changes to improvements in prosthesis function and patient outcomes based on available literature. Methods: Review and evaluation of the literature between 1973 and present describing modifications in IPP design and the influence of these modifications on IPP durability and patient‐related factors. Main Outcome Measures: Data describing the impact of iterative improvements in three‐piece IPP design on device function, durability, and patient outcomes. Results: There were progressive improvements in IPP technology from both major manufacturers not only on the durability of the prosthesis but also on patient outcomes, with fewer device failures and lower infection rates. Notable improvements include incorporation of kink‐resistant tubing, changes in the weave or addition of shear‐ and infection‐resistant coatings to cylinder layers, pump and tubing connection modifications, the addition of rear tip extenders, and the incorporation of lockout valves to prevent autoinflation. Conclusions: Numerous incremental modifications to the IPP from both major manufacturers since its invention have increased its durability and improved patient outcomes.Pastuszak AW, Lentz AC, Farooq A, Jones L, and Bella AJ. Technological improvements in three‐piece inflatable penile prosthesis design over the past 40 years. J Sex Med 2015;12(suppl 7):415–421.